Implementation of Ministry of Transportation Regarding Passenger Terminal Facilities Perspective Fiqh Siyasah - Khairunnas, Khairunnas; Lubis, Syofiaty (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
The terminal is a component of transportation that is used to lift and lower passengers. With this terminal, those seeking transportation will find it easier and more comfortable. This research will investigate how the implementation of the Minister of Transportation Regulation Number 24 of 2021 concerning the operation of road transport passenger terminal facilities at the Amplas type A terminal and the problems that occur in the community whether the existing facilities in this terminal have been properly used both in accordance with the regulations made by the government, as well as the study according to Fiqh Siyasah. Field research is used in this form of research. The findings demonstrate that the current facilities at the Amplas type A terminal are still not being utilized correctly, with numerous facilities being inoperable or underutilized. According to the study of Fiqh Siyasah, the government, which has supplied terminal facilities, has played a part in regulating the community in order for them to have comfort and goodness.